Environmental gradients and the evolution of tri‐trophic interactions. (28th November 2018) - Kergunteuil, Alan; Röder, Gregory; Rasmann, Sergio
Abstract: Long‐standing theory predicts herbivores and predators should drive selection for increased plant defences, such as the specific production of volatile organic compounds for attracting predators near the site of damage. Along elevation gradients, a general pattern is that herbivores and predators are abundant at low elevation and progressively diminish at higher elevations. To determine whether plant adaptation along such a gradient influences top‐down control of herbivores, we manipulated soil predatory nematodes, root herbivore pressure and plant ecotypes in a reciprocal transplant experiment. Plant survival was significantly higher for low‐elevation plants, but only when in the presence of predatory nematodes. Using olfactometer bioassays, we showed correlated differential nematode attraction and plant ecotype‐specific variation in volatile production. This study not only provides an assessment of how elevation gradients modulate the strength of trophic cascades, but also demonstrates how habitat specialisation drives variation in the expression of indirect plant defences.